2016
DOI: 10.1523/jneurosci.3670-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Prediction Error Links Excessive Amygdala Activation to Excessive Fear

Abstract: Basolateral amygdala (BLA) is critical for fear learning, and its heightened activation is widely thought to underpin a variety of anxiety disorders. Here we used chemogenetic techniques in rats to study the consequences of heightened BLA activation for fear learning and memory, and to specifically identify a mechanism linking increased activity of BLA glutamatergic neurons to aberrant fear. We expressed the excitatory hM3Dq DREADD in rat BLA glutamatergic neurons and showed that CNO acted selectively to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…We assessed nonspecific effects of DREADD expression and CNO injection on locomotor activity. Consistent with our past work (Yau and McNally, 2015;Sengupta et al, 2016;Choi and McNally, 2017;Gibson et al, 2018), there were none. We also showed that CNO injection in DREADD-expressing animals had no effect on expression of appetitive or aversive behaviors when these were assessed independently of each other.…”
Section: Methodological Considerationssupporting
confidence: 91%
“…We assessed nonspecific effects of DREADD expression and CNO injection on locomotor activity. Consistent with our past work (Yau and McNally, 2015;Sengupta et al, 2016;Choi and McNally, 2017;Gibson et al, 2018), there were none. We also showed that CNO injection in DREADD-expressing animals had no effect on expression of appetitive or aversive behaviors when these were assessed independently of each other.…”
Section: Methodological Considerationssupporting
confidence: 91%
“…Control injections were 0.5% DMSO in saline solution. Of the 22 articles that we found that used systemic administration of CNO in rats (Ferguson et al, 2011, 2013; Anderson et al, 2013; Michaelides et al, 2013; Boender et al, 2014; Bull et al, 2014; Dell’Anno et al, 2014; Kätzel et al, 2014; Robinson et al, 2014; Chang et al, 2015; Gompf et al, 2015; Mizoguchi et al, 2015; Pienaar et al, 2015; Scofield et al, 2015; Yau and McNally, 2015; Grace et al, 2016; Ma et al, 2016; Marchant et al, 2016; Qiu et al, 2016; Sengupta et al, 2016; Wicker and Forcelli, 2016; Wirtshafter and Stratford, 2016), 2 used chronic treatment (e.g., in drinking water) and 11 used doses >1 mg/kg. Of those that used doses of >1 mg/kg, most used doses of 3 mg/kg, but in a few cases doses were as high as 10 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…In this design, it is impossible to separate out the effects of activation of the DREADD from any unexpected effects of CNO, which could be the enhancement or blockade of the expected result of DREADD activation. In terms of dosing, a wide range of doses (0.2–10 mg/kg) is regularly used in DREADD experiments (Alexander et al, 2009; Ferguson et al, 2011, 2013; Ray et al, 2011; Agulhon et al, 2013; Anderson et al, 2013; Farrell et al, 2013; Michaelides et al, 2013; Wang et al, 2013; Boender et al, 2014; Bull et al, 2014; Dell’Anno et al, 2014; Kätzel et al, 2014; Robinson et al, 2014; Zhu et al, 2014; Chang et al, 2015; Gompf et al, 2015; Mizoguchi et al, 2015; Pienaar et al, 2015; Scofield et al, 2015; Yau and McNally, 2015; Grace et al, 2016; Ma et al, 2016; Marchant et al, 2016; Qiu et al, 2016; Sengupta et al, 2016; Wicker and Forcelli, 2016), and there is seldom any explanation given as to how the dose that was used was decided upon. Using the lowest effectual dose in the assay to be performed, that which in the non-DREADD-expressing animals is experimentally silent, would seem the most straightforward way to minimize any off-target effects of CNO.…”
Section: Relevance To the Dreadd System: Is Cno An Inert Ligand?mentioning
confidence: 99%
“…We used conditioned suppression of lever pressing as our measure of learned fear (Sengupta et al, 2016;Yau and McNally, 2015). Rats were trained to lever press to establish a stable baseline lever pressing response.…”
Section: Baseline Lever Pressingmentioning
confidence: 99%
“…These roles for BLA CaMKIIa in aversive prediction errors, memory consolidation, and other processes are likely embedded within distributed, multiplexed reinforcement signals (e.g., Roesch et al, 2012). They could involve distinct sub-populations of BLA CaMKIIa neurons or activity of the same or different neurons at different times during the conditioning trial (Likhtik and Paz, 2015;Livneh and Paz, 2012;Sengupta et al, 2016). Regardless, our data show that the primary behavioural consequence of BLA CaMKIIa optogenetic inhibition during reinforcement and non-reinforcement across fear conditioning, fear extinction, and conditioned inhibition, is a reduction in CS salience.…”
Section: Other Bla Camkiia Functions In Fear Learningmentioning
confidence: 99%